The ethics and economics of organoid commercialization: potential donors’ perspectives - Hanna de Groot; Manon van Daal; Regina W. Hofland; Inez Bronsveld; Karin R. Jongsma; Renske M.T. ten Ham (BMC Medical Ethics)
Abstract Advancing organoid technology requires human tissue donations and collaboration between researchers and commercial parties. However, many potential donors have reservations about commercial involvement in organoid research. To better understand these reservations, we conducted four focus groups with potential donors. Two focus groups were held with individuals with cystic fibrosis (n = 10). One focus group included individuals with neurodegenerative diseases (Parkinson’s or Huntington’s disease) (n = 4) and the other consisted of individuals with neurological disease (epilepsy) (n = 5). Four themes were identified: (1) benefits and concerns regarding commercial involvement, (2) trust in involved parties in research, (3) control over commercial parties and (4) appreciation of donors. To address these themes, we recommend that researchers and commercial parties communicate transparently and effectively, actively engage and appreciate donors, implement robust oversight mechanisms and (re)establish trust and trustworthiness through responsible practices. These considerations can help researchers and commercial parties work toward responsible and sustainable organoid research.